TAMING PLATFORM CAPITALISM: STRUGGLES FROM THE GLOBAL SOUTH MEET STRUGGLES FROM THE GLOBAL NORTH - Arriagada, Arturo; Graham, Mark; Huws, Ursula; Srinivasan, Janaki; Bonhomme, Macarena; Taduri, Pradyumna; Ustek-Spilda, Funda; Ferrari, Fabian; Bertolini, Alessio; Badger, Adam (AoIR Selected Papers of Internet Research, 2020)
This panel brings together scholars whose work seeks to tame platform capitalism understanding how the lives of platform workers are affected by digital platforms. Research on platform labor has been mostly done in the global north, as well as in relation to global platforms like Uber or Amazon (Rosenblat 2019; Scholz 2016). Thus, the panelists, moreover, explore how the lives of platform workers can be improved within the global platform economy by analyzing workers’ subjectivities in relation to platforms and the impact of technologies in job quality. To achieve this, this panel brings together scholars from global north and south countries that will map the complexities and subjectivities of platform workers in order to tame platform capitalism. We present a set of articles that address: (1) regulatory resistance that clarifies and redefines the rules that platforms need to abide by; (2) bottom-up resistance of platform workers who seek to organize, subvert, and build alternatives; (3) the ways that action research can support either of those initiatives to ultimately tame some of the worst excesses of platform capitalism.